2006
DOI: 10.1007/s00122-006-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome mapping among Picea glauca, P. mariana × P. rubens and P. abies, and correspondence with other Pinaceae

Abstract: A composite linkage map was constructed from four individual maps for the conifer Picea glauca (Moench) Voss, from anonymous and gene-specific markfers (714 AFLPs, 38 SSRs, and 53 ESTPs). A total of 12 linkage groups were delineated with an average marker density of 2.7 cM. Macro-synteny and macro-colinearity comparisons with two other composite linkage maps developed for the species complex P. mariana (Mill.) B.S.P. x P. rubens Sarg., and for P. abies (L.) Karst. revealed an identical number of linkage groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 92 publications
6
73
0
1
Order By: Relevance
“…Consequently, the number of markers segregating 3:1 was also likely inflated, particularly when considering that the parents originated from divergent sources (Jiggins et al 2005;Pelgas et al 2006). Overall, over one-third of the markers showed a 3:1 segregation ratio, which was much higher than the proportion expected by chance alone when using dominant markers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Consequently, the number of markers segregating 3:1 was also likely inflated, particularly when considering that the parents originated from divergent sources (Jiggins et al 2005;Pelgas et al 2006). Overall, over one-third of the markers showed a 3:1 segregation ratio, which was much higher than the proportion expected by chance alone when using dominant markers.…”
Section: Discussionmentioning
confidence: 98%
“…Small inversions were also observed between some linkage groups (e.g., LG4, Figure 2), and these were often associated with homologous loci informative in the opposite sexes between families. These inconsistencies in marker order were likely the result of doubtful positioning, particularly from loci considered as accessory markers within the current linkage map (Pelgas et al 2005(Pelgas et al , 2006). An additional explanation for noncolinearity may also be that despite the stringent criteria used for defining homology, homoplasy is still a likely source of mis-scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated maps not only increase the genome coverage but also make it possible to compare locations of major genes controlling important phenotypic traits or QTL positions between populations from multiple crosses. Although small chromosome rearrangements have been detected in some closely related species of the Pinaceae (Pelgas et al 2006) comparative mapping in the Rosaceae genus Prunus showed a very high degree of colinearity between the genomes of the diploid species peach, almond, apricot, and cherry (Dirlewanger et al 2004). Furthermore consensus maps of various genera of the Rosaceae have been linked with a conserved orthologue set of sequence-based markers (Sargent et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There can be little doubt that a DNA approach such as that reported by Ran et al (2006) will ultimately decide the matter, but molecular genetics investigations into white spruce done already have only begun to set the stage for achieving improved taxonomic resolution (e.g., Tulsieram et al 1992, Sigurgeirsson and Szmidt 1993, Smith and Klein 1994, Gosselin et al 2002, Gupta et al 2005, Nkongolo et al 2005, Pelgas et al 2006. Individuals within natural "white spruce" populations can present strikingly diverse phenotypes, and during sampling in support of DNA research decisions must be made regarding whether to "force" the diversity of phenotypes into the category "white spruce" or to split them into subgroups based on phenotypic differences.…”
Section: Some Speculation About the Scientific Importance Of Porsild mentioning
confidence: 99%